HUBUNGAN INTENSITAS BERMAIN GAME ONLINE DENGAN KECERDASAN EMOSIONAL PADA REMAJA DI SMP KRISTEN CITRA BANGSA KUPANG - Rexy Alexander Pakali Rexy; Maryati A Barimbing; Balbina Antonelda M wawo (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2022)
ABSTRACK Background : Online games are modern games that are in great demand by teenagers. Teenagers often play online games with excessive intensity, which is more than 2 hours or 2 times a day. In adolescence, emotional intelligence must also be formed properly through the way teenagers recognize and manage emotions. Research objective: to determine the relationship between the intensity of playing online games with the emotional intelligence of adolescents at Citra Bangsa Christian Junior High School Kupang. Research Methods: quantitative research with a correlation analytic research design with a cross sectional design The research sample amounted to 150 respondents who were selected by proportion sampling technique. Research results: the results obtained Value 0.467 with a value of = 0.05 then > which means there is no significant relationship between the intensity of playing online games with the emotional intelligence of teenagers Citra Bangsa Kupang Christian Middle School. Conclusion: teenagers who have a high intensity of playing online games do not guarantee that they will have low emotional intelligence or vice versa teenagers who have low intensity of playing online games do not guarantee that they will have good emotional intelligence. Keywords: Online Game, Emotional Intelligence, Adolescent